The Quality of Rice Straw by Fermented with Manure As a Feed Ruminant - Syamsu, Jasmal A (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
An experiment was conducted the quality of rice straw by fermented with manure as feed for ruminant. Materials used in this experiment were rice straw , manure and molasses. Four treatments rice straw + 3% molasses, B= rice straw + 3% molasses +30% manure. Parameters observed wereÂ organoleptic character , pH, crude protein, neutral detergent fiber ( NDF) and acid detergent fiber (ADF). The result of this experiment suggested that rice straw treated with manure 20% and 30% increased is crude protein and descreased its NDF and ADF. (Animal Production 3(2): 62-66 (2001)Key word: Rice straw, manure, fermentation, ruminant.